Epidemiology and placental pathology of intrauterine fetal demise in a tertiary hospital in the Philippines - Ourlad Alzeus G. Tantengco; Michele H. Diwa; Patrick Michael M. Millagrosa; Clarissa L. Velayo (Elsevier, 2024)
Objectives: The Philippines has at least 25,000 stillbirth or intrauterine fetal demise (IUFD) cases every year. Despite its burden, there is scarce information on IUFD epidemiology in the Philippines. Hence, this study reported the epidemiology and placental pathology of IUFD in a tertiary hospital in the Philippines. Study design: This cross-sectional study analyzed second- and third-trimester IUFD cases at the Philippine General Hospital from 2012 to 2021. We reviewed maternal sociodemographic and clinical characteristics and evaluated placental pathology. All statistical tests were done with GraphPad Prism software version 8.0. Results: We recorded 947 (2.28 %) cases of IUFD out of 41,562 obstetric deliveries from 2012 to 2021. Out of 947 IUFD cases, 532 had placental pathology reports. Second-trimester IUFD cases showed higher rates of no antenatal care (42.86 %) compared to third-trimester cases (10.61 %). Hypertensive disorders were more common in third-trimester IUFD. Infarcts (23.34 %), calcifications (4.12 %), and hemorrhages/hematomas (3.00 %) were the most prevalent placental abnormalities. While these abnormalities were more common in third-trimester IUFD, placental and fetal membrane infections like chorioamnionitis were more frequent in second-trimester IUFD. Conclusion: The results highlighted the differences in maternal sociodemographic and clinical characteristics, and placental pathology between second- and third-trimester cases of IUFD. These observations revealed distinct pathological processes and potential etiologies contributing to IUFD in the Philippines.